Childhood adversity and parenting behavior: the role of oxytocin receptor gene polymorphisms - Reichl, Corinna; Kaess, Michael; Fuchs, Anna; Bertsch, Katja; Bödeker, Katja; Zietlow, Anna-Lena; Dittrich, Katja; Hartmann, Annette M.; Rujescu, Dan; Parzer, Peter; Bermpohl, Felix; Resch, Franz; et al. (Journal of neural transmission, 2019)
Previous research revealed experiences of childhood adversity (CA) to be related to less favorable parenting behavior. It can further be expected that maternal oxytocin receptor (OXTR) genes may influence parenting behavior and moderate relationships between CA and parenting behavior. Moreover, associations between the OXTR gene and plasma oxytocin (OT) have been discussed. The present study investigated main effects of the OXTR gene on parenting behavior and plasma OT of mothers, and moderating effects of the OXTR gene on the relationship between mothers’ experiences of CA and parenting behavior. We relied on a sample of 193 mothers and their on average 8-year-old children. Maternal experiences of CA were assessed using a standardized interview. A questionnaire for the assessment of child abuse potential and observations of mother-child interaction were used as indicators of parenting behavior. For mothers, we analyzed three polymorphisms (rs53576, rs1042778, rs2254298) of the OXTR gene and plasma OT. Only the rs53576 was associated with mothers’ parenting behavior, specifically with maternal sensitivity. The rs2254298 significantly moderated relations between mothers’ experiences of CA and parenting behavior. Significant relations could be found only for mothers who were homozygous for the G allele. The G allele of the rs2254298 was further related to increased plasma OT levels. Our findings underline the importance of considering genetic variation when investigating consequences of CA and developing intervention programs that are adapted to an individual’s needs.